Sequential detention pond-biogeochemical barrier-free water surface wetland system for effluent purification and river eutrophication control. (June 2021) - Nsenga Kumwimba, Mathieu; Dzakpasu, Mawuli; Xinzhu, Li; Wang, Wei; Jie, Zhishi; Bao, Linlin; Su, Jingjun; Li, Xuyong
Abstract: Discharge of phosphorus (e.g., PO4 -P) and nitrogen (NO3 -N) from the wastewater treatment facility (WWTF) effluent even at low occurrence (e.g., μg PO4 -P L −1 ) could lead to eutrophication of receiving environments. Zhangjiakou city will host the international winter multi-sport event in 2022, which would probably yield a large amount of domestic WW and their associated contaminants in the water systems. To reveal the feasibility of an integrated surface flow constructed wetland (ISFCW) system for the purification of WWTF effluent, a field-scale ISFCW system was applied and operated in Zhangjiakou city. The ISFCW system consisted of a vegetated sedimentation pond (VSP) section followed by a biogeochemical barrier (BGB), and an SFCW. The purification performance of each purification component was monitored weekly over twelve months in terms of nutrient (N and P) removal. With the application of the ISFCW system, a total of 48.7, 59.4, 50.0, 54.9, and 60.2 % removal of TN, NH4 -N, NO3 -N, TP, and PO4 -P was achieved in the summer period. Further analysis demonstrated that the contributions of VSP, BGB and FTW to all analyzed nutrient removal were 3–78 %. The key removal processes appeared to be biological and physicochemical pathways, and the integration of the VSP, BGB and SFCW enhanced the purification capacity of the system. Overall, the ISFCW system was effective at reducing nutrients from WWTF effluent and could consequently be used locally and in other similar mountain-river systems. Additional optimization of operating conditions could result in an enhanced reduction of nutrients.